ANALISIS HUBUNGAN DINAMIKA KELOMPOK DENGAN TINGKAT PENERAPAN PENGELOLAAN TANAMAN TERPADU (PTT) DAN PRODUKTIVITAS USAHATANI PADI SAWAH DI DESA PALAS AJI KECAMATAN PALAS KABUPATEN LAMPUNG SELATAN - Sari, Ully Kartika; Viantimala, Begem; Nurmayasari, Indah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
The objectives of this research are to find out: (1) The dynamics of farmer group, (2) The lavel of integrated plant management implementation ‘PTT’ of paddy farmers group, (3) The productivity lavel of paddy farmers group, (4) The correlation between the lavel of farmers group dynamics with the integrated plant management implementation aplication rate, (5) The correlation between the lavel of farmers group dynamics with productivity lavel. This research was conducted in Palas Aji village, district palas, south lampung regency from April to Juni 2013. Fifty six farmers as respondents were selected by referring to Sugiarto et al. theory (2003). This research used survey method. Samples were taken using simple random sampling. Data were analyzed using descriptive method, and correlations among variables were tested using Rank Spearman’s correlation. The results showed that: (1) The dynamics group lavel included in dynamics category, (2) The lavel of integrated plant management implementation ‘PTT’ of paddy farmers group is at high category, (3) The productivity lavel of paddy farmers group has at 7,3 tons/ha average of value and included in medium category, (4) The correlation between the lavel of farmers group dynamics with the integrated plant management implementation result showed that related, (5) The correlation between the lavel of farmers group dynamics with productivity lavel result showed that related. Keywords : group dynamics, the integrated plant management implementation, productivity, paddy farmers